Pembuatan Mikrokristalin Selulosa dari Ampas Tebu (Saccharum officinarum L.) - Zulharmita, Zulharmita; Dewi, Siska Nola; Mahyuddin, Mahyuddin (Fakultas Farmasi Universitas Andalas, 2012)
A study on the preparation of microcrystalline cellulose from sugar cane bagasse (Saccharum officinarum L.) has been carried out. A total of 250 grams of dry sugar cane bagasse was made into alpha-cellulose by the method of multistage pulping and hydrolyzed with hydrochloric acid to produce microcrystalline cellulose which was further characterized. Microcrystalline cellulose were obtained as much as 71.5 grams with a yield of 28.6%. Characterization of microcrystalline cellulose from dry sugar cane bagasse, was done, including loss on drying, organoleptic, blue-violet coloured with of iodinated zinc chloride solution, soluble in the ammoniacal copper tetrammine solution, water-disoluble substances, not giving blue coloured with iodine 0.05 M, pH Â± 6 and absorbance spectrum using FT-IR spectrophotometer as same as the standard. It was concluded that microcrystalline cellulose from sugar cane bagasse and Vivacel PH 102Â® has fulfilled the requirements of British Parmacopoeia 2002.